Perubahan Sosial dan Pengaruhnya Terhadap Metode Ijtihad Imam Malik - Rahmad Fauzi Salim; M. Iqbal Irham; Sugeng Wanto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
Social change can occur due to many things. In general, social change can be caused by an increase in population, expansion of territory, revolution or rebellion in the country, even caused by conflict (social conflict) and others. During the time of Imam Malik, social changes occurred when the territory of Islamic rule expanded to various parts of the world. This situation prompted the Ulama to develop the ijtihad method to respond to new problems that arose in various Islamic jurisdictions. At that time, two streams of religious understanding appeared with different methods of understanding religious texts. Beginning with the emergence of a group of hadith experts or atsar experts who make the holy book and the traditions of the apostles the basis of religious understanding. Then came the ra'yi or ra'yu method expert group. This group uses a legal understanding of the scriptures and hadiths in a textual way, but puts forward the aims and objectives contained in the 'illah-'illah of the law of theorem. The Muslim community in the city of Medina represents a group of hadith experts. Meanwhile, the Islamic community living in Iraq represents the ra'yi expert group. So that the two streams have often debated in matters of religious understanding, especially fiqh, since the tabiin era.